Ventricular Dysfunction Secondary to Refeeding Syndrome in an Infant, A Case Report - Aristizabal, Ana M.; Guzmán-Serrano, Carlos A.; Ariza-Insignares, Camila; Guzmán, Gerardo; Guerrero, Claudia; Cely, Cesar (International Journal of Child Health and Nutrition, 2024)
Introduction: Refeeding syndrome is a complex of signs and symptoms that occur following the abrupt initiation of enteral or parenteral nutrition in malnourished patients, among other causes. Most data focuses on adolescents and adults, with limited neonatal information and other pediatric group ages. This case presents an infant who developed ventricular dysfunction due to refeeding syndrome following starvation. Case Report: A 5-month-old female with a one-month history of generalized maculopapular rash and lower limb edema. Physical examination revealed severe malnutrition and significant electrolyte imbalances. The initial echocardiogram was unremarkable. Despite nutritional and dermatological management, the patient developed respiratory distress, generalized edema, and anuria, necessitating Pediatric Intensive Care Unit admission. Subsequent echocardiograms revealed dilated cardiomyopathy with systolic-diastolic dysfunction. After receiving inodilator therapy and diuretics, her condition temporarily improved but deteriorated again, requiring further intensive care. Imaging ruled out significant structural heart disease, and after a prolonged hospital stay, the patient was eventually stabilized and discharged with gradual nutritional and growth improvement. Discussion: Cardiac complications following refeeding have been reported primarily in older patients with comorbidities, unlike our case, hence the rarity. Malnutrition-induced myocardial alterations and the stress of refeeding may have contributed to the observed ventricular dysfunction. Conclusion: Any malnourished patient should be considered for the potential onset of refeeding syndrome. Risks and complications should not be underestimated despite the patient's age. A multidisciplinary approach is crucial for the proper management of this condition, although its presence does not seem to warrant special considerations for the care of cardiac complications.